2012
DOI: 10.1364/ol.37.000767
|View full text |Cite
|
Sign up to set email alerts
|

Observation of vector solitons with hidden vorticity

Abstract: This letter reports the first experimental observation, to our knowledge, of optical vector solitons composed of two incoherently coupled vortex components. We employ nematic liquid crystal to generate stable vector solitons with counterrotating vortices and hidden vorticity. In contrast, the solitons with explicit vorticity and corotating vortex components show azimuthal splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
(17 reference statements)
2
18
0
Order By: Relevance
“…This is due to nonlocality as the nematic response extends far beyond the optical beams and acts as an attractive potential. This attraction of nonlinear beams in (nonlocal) liquid crystals is in accord with experimental observations [19,20] and theoretical results [29,57].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This is due to nonlocality as the nematic response extends far beyond the optical beams and acts as an attractive potential. This attraction of nonlinear beams in (nonlocal) liquid crystals is in accord with experimental observations [19,20] and theoretical results [29,57].…”
Section: Resultssupporting
confidence: 89%
“…By substituting (20) and the trial function (5) for the electric field E into the Green's function solution (4) for θ , and using the previously discussed asymptotic δ function approximation valid in the nonlocal limit to evaluate the resulting integral, the director angle for the half plane is…”
Section: B Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that one of the beams is a solitary wave and the other is a charge 1 optical vortex, as produced, for example, by a phase mask [21], a hologram [22], or a light modulator [23]. We consider light to propagate in the z direction, with x the polarization direction of the associated electric field.…”
Section: Modulation Equationsmentioning
confidence: 99%
“…These works have shown that the vector solitons with an explicit vorticity are always unstable against splitting in saturable nonlinear media [59]. In a recent paper the propagation of fundamental charged vortex pairs with hidden and explicit vortices was demonstrated experimentally in nematic liquid crystals [65], which shows that vortex pairs with hidden vorticity can be stable but vortex pairs with explicit vorticity always break up and transform into vector dipole solitons.…”
Section: Introductionmentioning
confidence: 99%